The impact of urological resection and reconstruction on patients undergoing cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) - Grace Hwei Ching Tan; Nicholas B. Shannon; Claramae Shulyn Chia; Lui Shiong Lee; Khee Chee Soo; Melissa Ching Ching Teo (Asian Journal of Urology)
Objective: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are increasingly being used to treat peritoneal malignancies. Urological resections and reconstruction (URR) are occasionally performed during the surgery. We aim to evaluate the impact of these procedures on peri-operative outcomes of CRS and HIPEC patients. Methods: A retrospective review of a prospectively maintained database of all patients who underwent CRS-HIPEC from April 2001 to February 2016 was performed. Outcomes between patients who had surgery involving, and not involving URR were compared. Primary outcomes were the rate of major complications and the duration of stay in the intensive care unit (ICU) and hospital. Secondary outcomes were that of overall survival (OS) and prognostic factors that would indicate a need for URR. Results: A total of 214 CRS-HIPEC were performed, 21 of which involved a URR. Baseline clinical characteristics did not vary between the groups (URR vs. No URR). Urological resections comprised of 52% bladder resections, 24% ureteric resections, and 24% involving both bladder and ureteric resections. All bladder defects were closed primarily while ureteric reconstructions consisted of two end-to-end anastomoses, one ureto-uretostomy, five direct implantations into the bladder and three boari flaps. URR were more frequently required in patients with colorectal peritoneal disease (p = 0.029), but was not associated with previous pelvic surgery (76% vs. 54%, p = 0.065). Patients with URR did not suffer more serious complications (14% vs. 24%, p = 0.42). ICU (2.2 days vs. 1.4 days, p = 0.51) and hospital stays (18 days vs. 25 days, p = 0.094) were not significantly affected. Undergoing a URR did not affect OS (p = 0.99), but was associated with increased operation time (570 min vs. 490 min, p = 0.046). Conclusion: While concomitant URR were associated with an increase in operation time, there were no significant differences in postoperative complications or OS. Patients with colorectal peritoneal metastases are more likely to require a URR compared to other primary tumours, and needs to be considered during pre-operative planning. Keywords: Cytoreductive surgery, Hyperthermic intraperitoneal chemotherapy, Peritoneal carcinomatosis, Urological procedures, Urological reconstruction